2021
DOI: 10.1186/s13018-021-02360-2
|View full text |Cite
|
Sign up to set email alerts
|

The effect of denosumab on pedicle screw fixation: a prospective 2-year longitudinal study using finite element analysis

Abstract: Background Pedicle screw loosening is a major complication following spinal fixation associated with osteoporosis in elderly. However, denosumab is a promising treatment in patients with osteoporosis. The effect of denosumab on pedicle screw fixation is unknown. Therefore, we investigated whether denosumab treatment improves pedicle screw fixation in elderly patients with osteoporosis. Methods This was a 2-year prospective open-label study. From Fe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 42 publications
0
19
0
1
Order By: Relevance
“…A prospective study utilized quantitative CT at baseline and 12 and 24 months in postmenopausal women with osteoporosis receiving denosumab and utilized finite element models of L4 to analyze bone strength and pedicle screw pullout. Their results showed improved BMD and pullout strength at 12 and 24 months compared with baseline 51 .…”
Section: Medical Managementmentioning
confidence: 95%
“…A prospective study utilized quantitative CT at baseline and 12 and 24 months in postmenopausal women with osteoporosis receiving denosumab and utilized finite element models of L4 to analyze bone strength and pedicle screw pullout. Their results showed improved BMD and pullout strength at 12 and 24 months compared with baseline 51 .…”
Section: Medical Managementmentioning
confidence: 95%
“…reported that HU value measured on CT was an independent predictor for pedicle screw loosening, and lower HU value was significantly correlated with higher risk of screw loosening ( 49 , 50 ). Another study showed that anti-osteoporosis treatment could achieve strong pedicle screw fixation effectively with an increase in bone mineral density around the screw assessed by QCT ( 51 ).Our results found lower bone quality in the convex vs. the concave side in the AV, AV ± 1, and AV ± 2 regions of the structural curve in AIS patients, suggesting that surgeons should exercise increased vigilance when selecting pedicle screw dimensions, a thicker and longer pedicle screw should be better to provide stronger holding force for internal fixation on the convex side during surgery when the width and length were suitable.…”
Section: Discussionmentioning
confidence: 99%
“…Mittlerweile findet auch zunehmend Denosumab, als Anti-RANKL-Antikörper, Anwendung in der Osteoporose-Therapie. In einer Kombination aus medikamentöser klinischer und chirurgischer Finite Element Analyse zeigte Denosumab eine verbesserte Schraubenbiomechanik [13]. Klinische Studien existieren auch in Kombination mit Teripraratid mit guten Ergebnissen für die Osteoporose, jedoch fehlenden Aussagen für spinale Operationen.…”
Section: Präoperative Möglichkeitenunclassified